Analisis Rantai Pasok (Supply Chain) Komoditas Cabai Rawit di Pasar Kalisat Kabupaten Jember - Febriviyanto, Galuh; Zuniana, Qory (KUBIS, 2023)
Chili is a commodity that is much loved by most people in Indonesia, besides that this one plant is easy to cultivate. Jember Regency is one of the chili producing places, precisely in Kalisat District with a cultivation area of around 521 ha. The aims of this research are (1). To find out the distribution flow of the Cayenne Pepper supply chain at Kalisat Market, Jember Regency, (2). To find out the Marketing Margin of Cayenne Pepper in the Jember Regency Kalaisat Market, (3). To find out the Efficiency of the Cayenne Pepper Marketing Channel at Kalisat Market, Jember Regency. The sampling method used in this research is purposive sampling. The results of this study indicate that 1) There are 2 marketing channels in Kalisat Market, namely: Channel I (Farmers/Producers-Resellers-Traders-Consumers), Channel II (Producers-Retailers-Consumers). 2) Margin for each marketing channel I is IDR 7,000, while Channel II is IDR. 3,000. 3) Efficiency Efficient marketing channel channel 1 is equal to 20% while channel II is equal to 8%. So the supply chain is used effectively, namely short channels because the costs incurred are not so large and high marketing profits can be suppressed.